FAKTOR-FAKTOR YANG MEMPENGARUHI FINANCIAL PERFORMANCE PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Aprillia, Winda; Nariman, Augustpaosa (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
This research aims to find out how working capital turnover, solvency, firm size, and sales growth affect financial performance in manufacturing companies in the goods and consumption industry sector with the food and beverage subsector listed on the Indonesia Stock Exchange during 2019-2021. The sample was selected by purposive sampling method with total sample of 22 food and beverages companies from a total population of 43 food and beverage companies. Data processing uses Eviews version 12 and Microsoft Excel. The result showed that working capital turnover, firm size, and sales growth have a positive and significant effect on financial performance. Solvability has a negative and significant effect on financial performance. The implications of this research is the need for an increase in working capital turnover, firm size, and sales growth which will affect the increase in the company’s financial performance.